Deskripsi Pelaksanaan Discharge Planning Di Ruang Rawat Inap - Rezkiki, Fitrianola; Fardilah, Velya Nelatul (REAL in Nursing Journal, 2019)
Discharge planning is part of the nursing process and the main function of the treatment. Discharge planning is an important stage that should be done. Small details of discharge planning are often overlooked and it often does when patient leaves hospital. This research aimed to overview Discharge Planning Implementation in Ambun Suri Inpatient Room of Dr. Achmad Mochtar Bukittinggi in 2019. The type of this study was quantitative descriptive. The populations were 182 patients. Then, by using accidental sampling technique, 65 patients were chosen as the samples. The data were collected through questionnaires and it was analyzed by univariate analysis. The results of this research showed that 33 people (50,8%) the discharge planning implementation was not optimal and 32 people (49,2%) respondents said that the implementation of discharge planning was optimal. In short, the implementation of discharge planning Inpatient Room is not optimal because nurses only performed important actions without paying attention to the details of the discharge planning measures.